Clinical Implications of Chloroquine and Hydroxychloroquine Ototoxicity for COVID-19 Treatment: A Mini-Review - Prayuenyong, Pattarawadee; Kasbekar, Anand V.; Baguley, David M. (Frontiers in Public Health, 2020)
At this time of COVID-19 pandemic, potentially effective treatments are currently under urgent investigation. Benefits of chloroquine and hydroxychloroquine for the treatment of COVID-19 infection have been proposed and clinical trials are underway. Chloroquine and hydroxychloroquine, typically used for the treatment of malaria and autoimmune diseases, have been considered for off-label use in several countries. In the literature, there are reports of ototoxic effects of the drugs causing damage to the inner ear structures which then result in hearing loss, tinnitus, and/or imbalance. This mini-review represents a summary of the findings from a systematic search regarding ototoxicity of chloroquine and hydroxychloroquine in the published literature. The characteristics of sensorineural hearing loss and/or tinnitus after chloroquine or hydroxychloroquine treatment can be temporary but reports of persistent auditory and vestibular dysfunction exist. These are not frequent, but the impact can be substantial. Additionally, abnormal cochleovestibular development in the newborn was also reported after chloroquine treatment in pregnant women. The suggested dose of chloroquine for COVID-19 infection is considerably higher than the usual dosage for malaria treatment, therefore it is plausible that the ototoxic effects will be greater. There are potential implications from this review for survivors of COVID-19 treated with chloroquine or hydroxychloroquine. Patient reports of hearing loss, tinnitus, or imbalance should be noted. Those with troublesome hearing loss, tinnitus and/or imbalance are encouraged to be referred for hearing evaluation and interventions once they are stable. Clinical trials of chloroquine or hydroxychloroquine should also consider including audiological monitoring in the protocol.